Number skills mobile application for down syndrome children - Ahmad, W.F.W. (Institute of Electrical and Electronics Engineers Inc., 2014)
Down syndrome (DS) children seem to have difficulties in learning numbers compared to reading. They need customized learning in numbers due to their slower pace of learning. Unfortunately, there is limited theory to guide DS children to learn and master in mathematics. With the advancement of technology, the learning style of special children has been improved from time to time from the paper and pen method, to the use of computer application such as courseware to the latest technology such as mobile application in smart phones and tablets. As for now, there is no personalized mathematics learning mobile application for DS children. The objectives of this paper are to report on the development of a mobile application on learning the basic numbers for DS children and to evaluate the user acceptance on the developed mobile application. The study will be focusing on the DS children with moderate level of IQ who are learning to recognize basic numbers. The method used to achieve the objectives is Rapid Application Development (RAD). The mobile application was developed using Eclipse Android Development Tool (ADT). An observation has been conducted to 5 DS children who have different level of IQ. The finding shows that the mobile application is really suitable for DS children who have moderate level IQ. Â© 2014 IEEE.